Kimura’s disease: A clinicopathological study of 23 cases - Lee, Chih-Chun; Yu, Kuang-Hui; Chan, Tien-Ming (Frontiers in Medicine, 2022)
Introduction: Kimura’s disease (KD) is an uncommon lymphoproliferative fibroinflammatory disorder. Patients present with head and neck subcutaneous nodules with or without lymphadenopathy. Peripheral blood eosinophilia and elevated serum immunoglobulin E (IgE) levels are typical. This study was designed to delineate the clinicopathological features, pattern of care, and disease course of 23 Taiwanese patients with KD. Methods: We retrospectively analyzed the clinical data of 23 consecutive cases (16 male and 7 female; age at diagnosis: 12–77 years) of KD diagnosed at our institution from 2015 to 2020. Results: The median time from presentation to diagnosis was 1 month. Twenty-one patients presented with either unilateral or bilateral head and neck masses. The remaining two presented with right flank and right arm lesions, respectively. Peripheral blood eosinophilia was observed in nine, and elevated IgE levels were observed in four. All were diagnosed using either excisional or core-needle biopsy. Seven patients underwent fine needle aspiration without a diagnostic yield. Salivary gland and lymph node involvement was observed in three and seven patients, respectively. Most lesions showed tissue eosinophilia (100%) and florid follicular hyperplasia (78.26%). Three cases had histological KD-IgG4RD overlap and three had comorbid IgG4RD were recognized. Thirteen patients underwent surgical resection, one received adjuvant therapy, and two received prednisolone monotherapy. Conclusion: KD should be considered in patients with subcutaneous masses, eosinophilia, and elevated IgE levels. Biopsy remains the gold standard of diagnosis. Increased recruitment of IgG4+ plasma cells is a common feature. IgG4RD in all KD patients may be prudent.